Paired box 6 gene delivery preserves beta cells and improves islet transplantation efficacy - So, Wing Yan (2024)
Loss of pancreatic beta cells is the central feature of all forms of diabetes. Current therapies fail to halt the declined beta cell mass. Thus, strategies to preserve beta cells are imperatively needed. In this study, we identified paired box 6 (PAX6) as a critical regulator of beta cell survival. Under diabetic conditions, the human beta cell line EndoC-βH1, db/db mouse and human islets displayed dampened insulin and incretin signalings and reduced beta cell survival, which were alleviated by PAX6 overexpression. Adeno-associated virus (AAV)-mediated PAX6 overexpression in beta cells of streptozotocin-induced diabetic mice and db/db mice led to a sustained maintenance of glucose homeostasis. AAV-PAX6 transduction in human islets reduced islet graft loss and improved glycemic control after transplantation into immunodeficient diabetic mice. Our study highlights a previously unappreciated role for PAX6 in beta cell survival and raises the possibility that ex vivo PAX6 gene transfer into islets prior to transplantation might enhance islet graft function and transplantation outcome.